Preparation and use of organic-inorganic hybrid ion exchangers in catalysis - Cardoso, Dilson; Martins, Leandro [UNESP] (Springer Nature, 2012)
Organic-inorganic hybrids constitute a new class of compounds in the research area of materials design. In this context, the preparation of hybrid organic-inorganic catalysts is presented, focusing on catalysts where an organic molecule is ionically bonded to the surface of an inorganic material. The application of this class of hybrid catalysts in some organic reactions is presented.